2017
DOI: 10.1038/s41598-017-11065-8
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular mechanisms underlying the involvement of the sigma-1 receptor in methamphetamine-mediated microglial polarization

Abstract: Our previous study demonstrated that the sigma-1 receptor is involved in methamphetamine-induced microglial apoptosis and death; however, whether the sigma-1 receptor is involved in microglial activation as well as the molecular mechanisms underlying this process remains poorly understood. The aim of this study is to demonstrate the involvement of the sigma-1 receptor in methamphetamine-mediated microglial activation. The expression of σ-1R, iNOS, arginase and SOCS was examined by Western blot; activation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Studies in animals and humans have shown that a significant rise in peripheral and brain inflammation signals exists following the chronic intake of most drugs of abuse [56][57][58][59]. The activation of microglia and/or astrocytes has been shown in animal models of every drug studied including amphetamines [60,61], cocaine [62], ethanol [63][64][65][66], opioids [67], cannabinoids [68,69], and nicotine [65,66]. Interestingly, though the different drugs of abuse exert different mechanisms to promote the release of dopamine in nucleus accumbens, and motivate consumption (Table 1), they exert similar mechanisms to increase both brain oxidative stress and neuroinflammation.…”
Section: Drug Consumption Promotes Brain Oxidative Stress and Neuroinmentioning
confidence: 99%
“…Studies in animals and humans have shown that a significant rise in peripheral and brain inflammation signals exists following the chronic intake of most drugs of abuse [56][57][58][59]. The activation of microglia and/or astrocytes has been shown in animal models of every drug studied including amphetamines [60,61], cocaine [62], ethanol [63][64][65][66], opioids [67], cannabinoids [68,69], and nicotine [65,66]. Interestingly, though the different drugs of abuse exert different mechanisms to promote the release of dopamine in nucleus accumbens, and motivate consumption (Table 1), they exert similar mechanisms to increase both brain oxidative stress and neuroinflammation.…”
Section: Drug Consumption Promotes Brain Oxidative Stress and Neuroinmentioning
confidence: 99%
“…The underlying mechanism of microglial activation induced by METH is related to the Toll-like receptor 4 (TLR4) located on microglia, which is involved in the immune surveillance of pathogens and exogenous small molecules ( Bachtell et al, 2015 ). Activation of microglia may also be mediated through the sigma-1 receptor, which involves ROS generation and activation of the mitogen-activated protein kinase (MAPK) and PI3K/Akt pathways in the neurotoxicity of METH ( Chao et al, 2017 ).…”
Section: Mechanisms Underlying Meth-induced Neurotoxicitymentioning
confidence: 99%
“…Evidence shows that Sig-1R may regulate microglia polarization. Chao reported that pretreating BV-2 cells with the Sig-1R antagonist BD1047 significantly reduced the methamphetamine-induced increased the ratio of M1 marker (iNOS) and M2 marker (Chao et al, 2017 ). An in vitro study shows that Sig-1Rs stimulation suppressed the morphological, migratory and the inflammatory responses of microglia to LPS (Hall et al, 2009 ).…”
Section: Sigma-1 Receptor and Microgliamentioning
confidence: 99%